Surgical Exposure and Orthodontic Treatment of Impacted Maxillary Central Incisors. A Case Report - Khudair A Al-Jumaili; Enas T Al-Jwary; Hind T Jarjees (University of Mosul, College of Dentistry, 2013)
Aims: This report describes a case of eleven years old female with impacted maxillary central incisors and presence of two supernumerary teeth .The surgical exposure and orthodontic traction of bilaterally impacted central incisors after removal of impacted supernumerary teeth is presented in this report. Materials and Methods: Clinical, radiographic follow-up and treatment was conducted at the department of orthodontic and maxillofacial surgery in the college of dentistry ,Mosul university .The surgical removal of supernumerary teeth done then surgical exposure and orthodontic traction done. Results: The impacted maxillary central incisors were successfully positioned and presented an acceptable gingival contour after treatment. Conclusion: Maxillary permanent central incisors were successfully positioned in the maxillary arch by surgical exposure and orthodontic traction, which showed good stability.